LUAS OPTIMUM PETAK UKUR UNTUK HUTAN TANAMAN KAYU PUTIH DI KESATUAN PENGELOLAAN HUTAN YOGYAKARTA (Optimum Size Of Sampling Plot For Cajuput Plantation at Forest Management Unit Yogyakarta) - Budi Mulyana; Rohman Rohman; Wahyu Wardhana (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2018)
Utilization of non-timber forest products, especially cajuput plants in Indonesia needs to be optimalized. The management of cajuput plantations should be supported with data and information toward sustainable management. The sampling approach to estimate the potential of cajuput leaves has no standard on plot size. The objective of this research is to determine the optimal plot size that can be used in inventory of cajuput plantation. Equipements used in this research are GPS, rope, bamboo, compass, digital scales, and quadcopter drones. The research material is cajuput stand which has good degree of normality. The method used in this research is making of nested sample plot of 20 x 20 m, 30 x 30 m, 40 x 40 m, 50 x 50 m, 60 x 60 m, 70 x 70 m, 80 x 80 m, 90 x 90 m, and standard plot (control) 100 x 100 m. Parameters measured were number of tree (n / ha) and the biomass of cajuput leaves-twig (Kg / ha). Data were analyzed by using t-student test to determine the difference of mean value between sample sample plot and control plot. The analysis is also done by calculating the precision of each sample plot. The result showed that the estimated value of number of tree (n / ha) of the 20 m x 20 m plot size was not significantly different with the control plot size of 100 m x 100 m. Estimation of leaves-twigs biomass of cajuput with plot size of 20 m x 20 m plot is also not significantly different with the result of measurement of leaves-twigs biomass of cajuput in control plot 100 m x 100 m. Thus, the optimum plot size that can be used in the study site is 20 m x 20 m.